Procesos pedagógicos en la enseñanza – aprendizaje de los estudiantes de 2do de secundaria del área de ciencia, tecnología y ambiente en la I.E Sefarín Filomeno - Lucana Ocampo, Edwin (2011)
The present investigation aims to determine the correlation between educational processes and teaching and leaming in the area of science, technology and environment of the second grade students of secondary education in the school Serafin Filomena Moyobamba in 201 O. The study is important because it allows to know the presence of pedagogical processes applied by the teachers in the teaching-learning process of students in the area in question. The aim of the research was to describe the relationship between the pedagogical processes of teaching and learning of students in second grade of secondary education in the area of science, technology and environment in the school Serafin Filomena Moyobamba in 201 O, and Specific objectives were to identify the pedagogical processes used by teachers in second grade of secondary education, describe the teaching-learning students in second grade of secondary education and analyze the relationship between the pedagogical processes of teaching and learning of students second grade of secondary education. Pedagogical processes are supported by the Ministry of Education, the National Directorate of Basic Education, Santillana, Taylor, V. and chips, L., who claim that these processes should be developed in each training session, and the teaching-learning process in the natural sciences, Tovar Ruiz-Gálvez and F. They give us enough theoretical tools to pose the following hypothesis: There is a relationship between the pedagogical processes of teaching and leaming of second grade students of secondary education in the area of science, technology and environment at the school in Serafin Filomena Moyobamba 201 O. Methodologically, the research design was descriptiva correlational study, with a sample of 56 students in second grade "A" and "G" of secondary education in the school "Serafin Filomena," and in the process of statistical analysis that was obtained accept the hypothesis or research center with a 95% confidence, the same is evident in the graph of the Gaussian curve and the value that was obtained from the Pearson correlation coefficient being mean and a positiva correlation that is explained by 8. 70% of the population. 16